Internal Medicine Nurses' Attitudes towards Evidence-Based Nursing - Tuğba Menekli; Medet Korkmaz (Dokuz Eylul University, 2021)
Background: Health care approach in evidence is very important in clinical decision making. The care decision is based on the best evidence available, clinical experience and patient preferences, it was decided. Objective: The aim of this study is to ensure that nurses working in internal medicine clinics have evidence-based nursing to determine their attitudes towards. Methods: This descriptive study was conducted between May 2018 and December 2018 with 964 nurses working in hospitals in Sanliurfa. The explanation of the study was collected with "Nurse Information Form" and "Attitude Scale towards Evidence-Based Nursing". The analysis of the data was done in SPSS 23.0 program. Results: It was determined that 65.7% of the nurses used evidence-specific preferences in their nursing practices and 63.1% of them did not know if you can access the evidence that includes nursing. The mean score of the eler Evidence Based Nursing Scale of the nurses was 43.53 ± 3.08; Beliefs and expectations for proven nursing are 23.18 ± 2.07, 11.44 ± 3.16 and 11.44 ± 3.16, respectively. It was determined that the total attitude scores of the nurses aged 25 and under, working as a responsible nurse for 1-6 years, conducting scientific research and attending the meetings were significantly higher. Conclusion: Attitudes of nurses working in treatment clinics towards proven nursing are moderate and need to be improved.